2000
DOI: 10.1002/(sici)1099-1743(200003/04)17:2<117::aid-sres288>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of systems science to the development of the decision support system subspecialties: an empirical investigation

Abstract: This is a comprehensive study that, by means of an empirical assessment of the decision support systems (DSS) literature over the past 23 years (1971–1993), systematically identifies the DSS reference disciplines and traces how concepts and findings by systems researchers have been picked up by DSS researchers to be applied, extended and refined in the development of DSS research subspecialties. Cluster analysis was applied to an author cocitation frequency matrix derived from a comprehensive database of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
(81 reference statements)
0
11
0
1
Order By: Relevance
“…Further details on earlier contributions of Systems Science in the 1970s and 1980s can be found in comprehensive reviews related to the fields of IS research (see Xu, 2000), Decision Support Systems (see Eom, 2000), and Information Resources Management (see McLeod, 1995). Mora, Gelman, Forgionne, Petkov, and Cano (2007) presented a critique and integration of the main IS research paradigms and frameworks reported in the IS literature using a systems approach.…”
Section: On Critical Systems Thinking Multimethodology and Ismentioning
confidence: 99%
“…Further details on earlier contributions of Systems Science in the 1970s and 1980s can be found in comprehensive reviews related to the fields of IS research (see Xu, 2000), Decision Support Systems (see Eom, 2000), and Information Resources Management (see McLeod, 1995). Mora, Gelman, Forgionne, Petkov, and Cano (2007) presented a critique and integration of the main IS research paradigms and frameworks reported in the IS literature using a systems approach.…”
Section: On Critical Systems Thinking Multimethodology and Ismentioning
confidence: 99%
“…Fortunately, some social work researchers have broached this topic over the years, most notably Monnickendam (e.g., Monnickendam, Savaya, & Waysman, 2005). To guide other social work researchers in this area and extend conceptual frameworks beyond Beer, information systems and other researchers have approached this topic via decision support systems (Ba, Stallaert, & Whinston, 2001;Eom, 2000;Mohan, Muse, & McInerney, 1998), decision-making (Bharwani, 2006), design science (Carlsson, 2007), and knowledge management (Henry, 1974). Indeed, Maier and Hadrich's (2011) text on knowledge management systems covers the fundamentals of knowledge management from the inception of data, to information, and on to the culmination of knowledge that impacts organizational functioning.…”
Section: Feedback Loopmentioning
confidence: 99%
“…A recent study has systematically identified DSS reference disciplines and traced how concepts and findings by systems researchers have been picked up by DSS researchers to be applied, extended and refined in developing DSS research subspecialities. According to the study, in the early stages of DSS development it was systems science that provided an essential concept for defining the concept of decision support systems and justifying the need for such systems in organizations (Ackoff, 1967;Eom, 2000). In addition, systems theory provides a useful principle in solving strategic and operating problems; cybernetics has played an important role in designing DSS as well as management information systems; and DSS development has been assisted by systems theory such as SSA and WSR (Takahashi and Takahara, 1995;Takahara and Shiba, 1996;Eom, 2000;Zhu, 1998Zhu, , 2000.…”
Section: Decision Support Systems (Dss)mentioning
confidence: 99%
“…Systems theory has been considered as the basis for information systems, and has been applied to or proposed to be applied to information systems research (Muller-Merbach, 1983;Schoderbek et al, 1985;Xu, 1987Xu, , 1991Xu, , 1995Xu and Li, 1989;Newman, 1989;Stowell, 1993;Cheng and Tang, 2000;Eom, 1998Eom, , 2000Li, 2000;Zhu, 1998Zhu, , 2000. A wealth of research in information systems in the framework of systems theory has produced an astonishing array of theoretical results and empirical insights, and a large suite of tools and methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation